2007
DOI: 10.1097/01.ccm.0000288104.97602.b3
|View full text |Cite
|
Sign up to set email alerts
|

Near-fatal pediatric asthma managed with pumpless arteriovenous carbon dioxide removal*

Abstract: Percutaneous cannulation with a simplified pumpless extracorporeal circuit is capable of removing sufficient carbon dioxide to allow application of a protective ventilatory strategy in severe hypercapnic pediatric respiratory failure. The procedure was safely applied without complications in four pediatric patients as young as 4 yrs of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Volume of blood in this circuit is approximately 290 cc, of which nearly 270 cc lies in the oxygenator. [34]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume of blood in this circuit is approximately 290 cc, of which nearly 270 cc lies in the oxygenator. [34]…”
Section: Discussionmentioning
confidence: 99%
“…[3] Only one case series of pediatric asthma managed with AVCO 2 R have been reported. [4] We report a case of life-threatening asthma that developed severe hypercapnia and acidosis on mechanical ventilation and was successfully managed with AVCO 2 R.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ECLS has been used in severely injured patients with refractory hypoxemia [1113]. Similarly, ECLS has been used for patients with tracheobronchial injuries [14] and for severe acute asthma [8, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients in status asthmaticus placed on ECMO have had a reversal of hypercapnia and acidosis in as little as 2-4 h of treatment (29,30). At present, there are no evidence-based guidelines on when to initiate ECMO for status asthmaticus, but a study by Kukita et al has suggested use in the setting of persistent hypoxemia, pH < 7.2, PCO 2 > 100 mm Hg, or in the face of life-threatening complications due to ventilation, such as hypotension or barotrauma (31).…”
Section: Indicationsmentioning
confidence: 99%